Kegiatan Ekonomi Dalam Pemberdayaan Masyarakat di Kampung Maredan Barat, Tualang, Kabupaten Siak - Denisa Damayanti; Said Suhil Ahmad; Muhammad Jais (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine and analyze how economic activities in community empowerment in the village of West Maredan. This study used descriptive qualitative method. Qualitative research aims to describe a careful reality of a phenomenon that occurs. Data collection uses documentation, observations and interviews about economic activities in community empowerment. The results showed that in the sustainability of economic activities the two home industries studied, namely the tofu home industry and the brown sugar home industry, had 3 indicators in carrying out economic activities, the first was the production process, the production process that occurred both in the brown sugar home industry and the tofu home industry. in West Maredan still use the traditional system because the equipment used is not modern, in production activities there is no significant difference from both the tofu industry and the palm sugar industry. For tofu factories, the production process does not require extra effort, in contrast to palm sugar, it requires the help of 2 to 3 people starting from the process of felling palm trees and the process of cutting palm oil to be processed again. Economic activities will not be separated from distribution, distribution activities for the two home industries are carried out by delivering them to the nearest shop and market, there are also some middlemen who go directly to production sites, targets or consumers from the two home industries, not only people around Maredan Barat, but already some came from outside the region such as Pekanbaru, Duri and Siak. With the existence of economic activities in the West Maredan village, at least 15% of the community has been able to empower and ease the burden on several people who depend on their work from the production of these two home industries. Judging from the residents of Maredan Barat, there are 2,341 people and there are 10-12 buyers every day, so 20% of the production every day is always sold out. Keywords: economic activity, empowerment, public